Mango Postharvest Best Management Practices Manual - Jeffrey K. Brecht; Steven A. Sargent; Adel A. Kader; Elizabeth J. Mitcham; Fernando Maul; Patrick E. Brecht; Octavio Menocal (EDIS)
Improving the quality and consistency of the fresh mangos that are available to consumers in the United States is an important goal of the National Mango Board (NMB). The NMB-funded project, Monitoring and Evaluation of the Mango Supply Chain to Improve Mango Quality (referred to hereafter as the Mango Quality Project), was conducted from December 2007 through April 2009 to identify impediments to successfully meeting that goal. The final deliverable of the Mango Quality Project is this best management practices manual for harvesting and handling mangos marketed in the US. The manual includes quality-control procedures to use when monitoring the maturity and quality of mangos in commercial handling operations.